The Design of Language Testing and Evaluation Materials for the English Department - Irra Wahidiyati; Windhariyati Dyah K; Ghaida Thifal (Tarling : Journal of Language Education, 2026)
Background - The students of Tadris Bahasa Inggris need explicit material about assessments and tests. They need the material to develop listening and speaking skills. Next, the TBI students must master the creation of writing and reading test items. In addition to creating writing and reading test items. Urgency of Research – The needs analysis shows that students’ needs regarding the Language Testing and Evaluation subjects in the English Department of UIN Prof. K. H. Saifuddin Zuhri Purwokerto. They need information on how to create assessment rubrics for them. The learning materials used are compiled to meet the students' needs. Research Objectives – This study conducts a needs analysis of students' needs regarding the Language Testing and Evaluation subject and designs new material for it. Research Method - A mixed method was used to answer the research questions. The researcher analyzed the institution's problems and assessed whether students' needs aligned with the syllabus or lesson plan. The information sources were 100 students and 2 lecturers. Research Findings – The draft of the material consists of 7 chapters. Chapter 1 discusses assessment concepts and issues. Chapter 2 discusses the principles of language assessment. Chapter 3 discusses the design of classroom language tests and standardized testing. Chapter 5 discussed the assessment of listening, including intensive, responsive, selective, and extensive listening. Chapter 6 discusses assessing speaking, including imitative, intensive, responsive, interactive, and extensive speaking. Chapter 7 discusses the assessment of reading, including perceptive, selective, interactive, and extensive reading. Chapter 8 discusses assessing writing, including imitative, intensive, responsive, and extensive. Chapter 9 discusses the assessment of grammar and vocabulary. The last chapter discusses the grading and evaluation process. Research Conclusion & Novelty - The materials integrate assessment theory, test construction, and rubric development for all language skills into a single contextualized resource designed to promote Language Assessment Literacy.